Economic ties of Bosnia and Herzegovina and its neighbors within the Kingdom of Serbs, Croats and Slovenes - Užičanin, Salkan (Historical Thought, 2025)
After the First World War economic ties which Bosnia and Herzegovina had prior to entering the Kingdom of SHS were broken and normal cooperation with neighbours, which had had various political and economic orders before the unification, very difficult, due to unstable political and economic conditions within the common state. Linking these disparate economic systems into a single economic entity for a number of problems occurred slowly. However, despite all the difficulties, immediately after the unification, there began the establishment of economic relations between neighbours. First it was started with trade and traffic, and then and other business relationships. However, it turned out that the economic ties only with neighbours were insufficient, due to which some earlier, primarily trade relations with foreign countries were renewed.